Knowledge Synthesis: Underrepresentation of Indigenous Students in Canadian Post-Secondary Institutions - Novak, Hélène; Dhungel, Rita (Journal of Advanced Academic Research, 2024)
This article will explore barriers for Indigenous students to pursuing and persisting with university education in Canada. Canada has favored a Eurocentric curriculum throughout history discrediting Aboriginal knowledge bases and values including Indigenous languages. As a result of Western assimilation policies which were institutionalized through the 1876 Indian Act and the Indian Residential School System (IRSS), Aboriginal communities have suffered tremendously. The educational journeys of Indigenous peoples are inadequate. Through a compressive literature review, this article will critically examine the relationships between intergenerational trauma (IGT) experienced by Indigenous communities and its’ role in students' underrepresentation within Canadian post-secondary institutions. For the purpose of this paper, thirteen literature including peer-reviewed and grey literature were thoroughly examined. Key finding of the review will be presented in this knowledge synthesis paper.